Triple diffusive convection of non-Newtonian fluid subject to compressibility and suspended particles - Aggarwal, A. K.; Dixit, Dhruva (AIP conference proceedings, 2020)
In this paper, we are considering triple diffusive convection of compressible fluid layer (Rivlin-Ericksen) when the medium is porous. This layer is permeated with suspended particles. The effect of solute gradients, medium permeability, compressibility and suspended particles is investigated. It is observed that, for stationary convection, solute gradients stabilize the system. Medium permeability, compressibility and suspended particles destabilize the system.